Establishment of a Micropropagation Protocol for Elite Accessions of Bael (Aegle marmelos (L.) Corr.), a Tropical Hardwood Species - Chamila Pathirana; Udayanthi Attanayake; Udula Dissanayake; Lakshman Gamlath; Kalyani Ketipearachchi; Terrence Madhujith; Janakie Eeswara (Advances in Agriculture)
The limited availability of high-quality planting material hinders the popularization of bael (Aegle marmelos (L.) Corr.) as a profitable cash crop in Sri Lanka. Five elite bael accessions, namely, Beheth Beli, Paragammana, Mawanella, Rambukkana, and Polonnaruwa-Supun, have been identified and used for mass propagation through budding and grafting. However, this process gets hampered by the limitations in large-scale production of planting material. Micropropagation is an alternative technique to produce clonal plants in large-scale; however, no established protocol is available for the field-grown elite bael accessions in Sri Lanka, and hence, the present study was conducted. The best sterilization method was found to be the washing of explants in a 2.5% fungicide solution for two hours. The full MS and ½MS media provided significantly similar performance in shooting, as indicated by the measured parameters. The twig plants did better than leaf explants concerning shoot extension, in which twig explants yield 1.33 cm taller shoots. The 1 mg/l of BAP concentration generated the highest number of shoots (6.20) and the most extended shoots (3.83 cm). The most successful rooting (60% success) was spotted with full MS, 1 mg/ml NAA, and 3% sugar. As previously reported, the successful micropropagation is possible if the explants are harvested from April to June, immediately after the fruiting season of the plant. The established protocol can mass-produce clonal bael plants from the elite accessions.